Trends in Source and Age Verification for Beef Calves Sold via Summer Video Auction from 2010 Through 2017 - E. D. McCabe; M. E. King; K. E. Fike; K. L. Hill; G. M. Rogers; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:The objective of this study was to quantify the effect of source and age verification status on the sale price of beef calf lots sold via summer video auctions from 2010 through 2017 while adjusting for all other factors that significantly influenced sale price. Study Description:Information describing factors about lots sold through a livestock video auction service (Superior Livestock Auction, Fort Worth, TX) was obtained from the auction service in an electronic format. These data were collected for 36,570 lots of beef calves that were sold via 61 summer sales from 2010 through 2017. A model was developed for each year to quantify the effects of all factors describing beef calf lots that significantly affected sale price. The Bottom Line:Though the percent of lots qualified for source and age verification decreased from 2011 to 2016, premiums were garnered from verified lots. The percentage of lots enrolled may continue to increase with new export markets.
Keywords: beef calves; source and age verification; video auctions